UTILIZATION STRENGTHENING NATIONAL IDENTITY OF NUMERAL CLASSIFIER WORDS IN TRADING AT MODERN MARKET - Nadra Nadra; Sri Wahyuni (International Conference on Languages and Arts, 2014)
Problematic utilization of words and terms in Indonesian language is various and complex. One of them can be identified as utilization of numeral classifiers in trading activity, especially at modern market. Most of numeral classifier words that are used in that situation do not come from Indonesian language, they are derived from foreign languages, especially English. Meanwhile Indonesian language has much varied words and terms in the numeral classifier. As a result, there are number of words in Indonesian numeral classifier that begin to disappear or are not used anymore. As the national language and the language of the country, it is obligation to Indonesian to maintained, nurtured, and developed it. Maintaining the Indonesian language is necessary in order to maintaining the national identity of Indonesia. In other hands, nurturing Indonesian language is very important to straighten the standardized Indonesian language. Whereas in the context of development, Indonesian language must be developed by referring to the word or term that already existed in Indonesia rather than form other languages. Based on these three aspects, it can be clearly seen that Indonesian language as National Identity of Indonesia, especially in utilization of numeral classifier words in trading activities at modern market, has not functioned appropriately. Therefore, utilization of numeral classifier words at the modern market must follow the Indonesian language guidance to strengthen Indonesian National Identity and to avoid the existing numeral classifiers of Indonesian language from becoming archaic words.   Keyword: archaic, identity, trading, numeral classifier words, modern market